Effect of the metallic oxides mix-doping on the microstructure and superconducting properties of Bi-2223 Ag/tapes. (July 2020) - Lu, X Y; Yi, D; Nagata, A
Abstract: The Bi-2223 Ag/tapes with the composition Bi1.8 Pb0.4 Sr1.9 Ca2.1 Cu3.5 Oy + Xn (X1: un-doped; X2: 1wt% MgO + 1wt% Ag2 O; X3: 1wt% MgO + 1wt% Ag2 O + 0.05wt% SnO2 ; X4: 1wt% MgO + 1wt% Ag2 O + 0.05wt% B2 O3 ; X5: 1wt% MgO + 1wt% Ag2 O + 0.05wt% Li2 O; X6: 1wt% MgO + 1wt% Ag2 O + 0.05wt% La2 O3 ) were prepared by sintering at 837°C for 120 h after partial-melting at 850°C for 1 h. The B2 O3 mix-doped tape (X4) and the Li2 O mix-doped tape (X5) shows lower conversion of Bi-2212 phase to Bi-2223 phase and lower J c value than the un-doped tape (X1). The MgO and Ag2 O mix-doped tape (X2) shows the same conversion of Bi-2212 phase to Bi-2223 phase as the un-doped tape (X1), but higher J c value than the un-doped tape (X1). The SnO2 mix-doped tape (X3) and the La2 O3 mix-doped tape (X6) show higher conversion of Bi-2212 phase to Bi-2223 phase and higher J c value than the un-doped tape (X1). However, the La2 O3 mix-doped tape (X6) shows the highest proportion of Bi-2223 phase and the highest critical current density. It is suggested that the critical current density depends on the flux pinning and the conversion of Bi-2212 phase to Bi-2223 phase. The MgO doping can increase J c due to improving the flux pinning, and the SnO2 mix-doping and La2 O3 mix-doping can increase J c due to increase the conversion of Bi-2212 phase to Bi-2223 phase.